Prove that the sequence $\sqrt{2} , \sqrt{2\sqrt{2}}, \sqrt{2\sqrt{2\sqrt{2}}}$ converges to 2

My attempt

I proved that the sequence is increasing and bounded by 2, can anyone help me show that the sequence converges to 2? Thanks for your help

  • 2
    $\begingroup$ you actually know that it converges to 2? $\endgroup$ – HipsterMathematician Sep 21 '12 at 18:19
  • $\begingroup$ No,That's all I need to prove $\endgroup$ – Miguel Mora Luna Sep 21 '12 at 18:21
  • $\begingroup$ @kingW3: Oops, I completely misread the question. I've retracted my close vote. $\endgroup$ – Rahul May 28 '17 at 16:53
  • $\begingroup$ @Rahul Just wanted to point that out :P (as a side note I voted to reopen the other two questions so they can be correctly closed as dupes) $\endgroup$ – kingW3 May 28 '17 at 22:02

Another prove:

Notice that: $a_1 = 2^{1/2},\ a_2 = 2^{3/4},\ a_3 = 2^{7/8}$, and so on, thus, $$a_n = 2^{(2^n-1)/2^n} = 2^{1-1/2^n}$$

Taking limit as $n$ tends to infinity, we have that $$\lim_{n \rightarrow \infty} a_n = 2^1 = 2$$


We have

$$\sqrt{2}=2^{\frac{1}{2}}.$$ Exciting, no? We also have $$\sqrt{2\sqrt{2}}=2^{\frac{1}{2}+\frac{1}{4}},$$ and $$\sqrt{2\sqrt{2\sqrt{2}}}=2^{\frac{1}{2}+\frac{1}{4}+\frac{1}{8}}.$$ For the next term, we take the previous term, multiply by $2$, getting exponent of $2$ equal to $1+\frac{1}{2}+\frac{1}{4}+\frac{1}{8}$, then take the square root, getting exponent of $2$ equal to $\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}$. The pattern continues, since the "next term" is always obtained by the same process.

It is well-known that the series $\frac{1}{2}+\frac{1}{4}+\frac{1}{8}+\frac{1}{16}+\cdots$ converges to $1$. Since the function $f(x)=2^x$ is continuous, our original sequence converges to $2^1$.

  • 18
    $\begingroup$ Awesome answer. $\endgroup$ – ThomasMcLeod Sep 22 '12 at 3:20
  • 1
    $\begingroup$ +1, Great answer. indeed. :-) Not even god knows why this was not accepted or rather is still not accepted. $\endgroup$ – SchrodingersCat Dec 15 '15 at 8:57
  • 2
    $\begingroup$ Awesome. A no-nonsense, soul-satisfying kind of answer. Love it. $\endgroup$ – Mallory May 12 '16 at 4:51


$$a_n:=\underbrace{\sqrt{2\sqrt{2...\sqrt 2}}}_{n\text{ square roots}}\Longrightarrow a_n=\sqrt{2a_{n-1}}$$

Since you've already proved the sequence $\,\{a_n\}\,$ converges, assume its limit is $\,x\,$ , so

$$x=\lim_{n\to\infty}a_n=\lim\sqrt{2a_{n-1}}=\sqrt{2x}\Longrightarrow x^2=2x$$

and since it's trivial that $\,x\neq 0\,$ then you can cancel above and get what you want.


Hint : let $y = \sqrt{2.{y}}$ , Now solve for y.

  • $\begingroup$ Why did you make that y? $\endgroup$ – Miguel Mora Luna Sep 21 '12 at 18:24
  • $\begingroup$ I also planned to do that but not to give justification $\endgroup$ – Miguel Mora Luna Sep 21 '12 at 18:25
  • 5
    $\begingroup$ @MiguelMoraLuna: quartz is computing the steady-state of the iteration $x_{k+1} = \sqrt{2 x_k}$. $\endgroup$ – Rod Carvalho Sep 21 '12 at 19:11
  • $\begingroup$ You'll also need to prove that x isn't 0 for this approach to work. $\endgroup$ – David Bandel Jul 13 '16 at 3:43

Consider the following discrete-time dynamical system (or "infinite state machine", if you prefer)

$$x_{k+1} = \displaystyle\sqrt{2 x_k}$$

where $x_0 = \sqrt{2}$ is the initial condition. Let us introduce function $f (x) := \sqrt{2 x}$ so that the state-transition equation can be written in the form $x_{k+1} = f (x_k)$. You want to prove that

$$x_{\infty} := \displaystyle\lim_{k \rightarrow \infty} x_k = 2$$

Does $x_k$ converge to $2$? Here's a short numerical experiment in Haskell (using GHCi):

*Main> let f x = sqrt (2 * x)
*Main> let x0 = sqrt (2)
*Main> let xs = iterate f x0
*Main> take 10 xs

Looks like $x_k$ does indeed converge to $2$. Let's now try to prove it. I introduce a new symbol

$$\tilde{x}_{k} := \ln (x_k)$$

which allows us to rewrite the state-transition equation $x_{k+1} = \displaystyle\sqrt{2 x_k}$ in the following form

$$\tilde{x}_{k+1} = \frac{1}{2} \tilde{x}_k + \ln(\sqrt{2})$$

which is a scalar linear dynamical system of the form $s_{k+1} = a s_k + b$, whose general solution is

$$s_ k = a^k s_0 + \displaystyle\sum_{i=0}^{k-1} a^i b$$

Therefore, we obtain the following general solution

$$\tilde{x}_k = \left(\frac{1}{2}\right)^k \tilde{x}_0 + \displaystyle\sum_{i=0}^{k-1} \left(\frac{1}{2}\right)^i \ln(\sqrt{2})$$

and, taking the limit

$$\tilde{x}_{\infty} := \displaystyle\lim_{k \rightarrow \infty} \tilde{x}_k = \displaystyle\lim_{k \rightarrow \infty} \sum_{i=0}^{k-1} \left(\frac{1}{2}\right)^i \ln(\sqrt{2}) = \left[\sum_{i=0}^{\infty} \left(\frac{1}{2}\right)^i\right] \ln(\sqrt{2}) = 2 \ln (\sqrt{2}) = \ln (2)$$

and, finally, we conclude that $x_{\infty} = \exp(\tilde{x}_{\infty}) = 2$.


Let us denote your sequence by $x_n$. Then $$ x_1=\sqrt{2},\ x_{n+1}=\sqrt{2x_n} \quad \forall\ n \ge 1. $$ Clearly $\sqrt{2}\le x_n<2$ for every $n \ge 1$, and $$ x_n-x_{n+1}=x_n-\sqrt{2x_n}=\frac{x_n^2-2x_n}{x_n+x_{n+1}}=\frac{x_n(x_n-2)}{x_n+x_{n+1}}<0 \quad \forall n \ge 1. $$ Hence $(x_n)$ is increasing and bounded above. It follows that $(x_n)$ is convergent. If $l$ denotes its limit, then $\sqrt{2}\le l \le 2$ and $l=\sqrt{2l}$. Solving the equation $l=\sqrt{2l}$ we get $l\in \{0,2\}$, and since $\sqrt{2} \le l \le 2$, we deduce that $l=2$.


You can also observe that

$$\sqrt{2\sqrt{2\sqrt{2 ...\sqrt{2}}}} \cdot \sqrt{\sqrt{\sqrt{...\sqrt{2}}}}=2$$


$$\sqrt{2\sqrt{2\sqrt{2 ...\sqrt{2}}}} =\frac{2}{\sqrt[2^n]{2}}$$


protected by Community Sep 3 '15 at 2:44

Thank you for your interest in this question. Because it has attracted low-quality or spam answers that had to be removed, posting an answer now requires 10 reputation on this site (the association bonus does not count).

Would you like to answer one of these unanswered questions instead?

Not the answer you're looking for? Browse other questions tagged or ask your own question.